1980
DOI: 10.1136/jmg.17.3.161
|View full text |Cite
|
Sign up to set email alerts
|

Screening of thalassaemia carriers in intermediate school of Latium: results of four years' work.

Abstract: This project is aimed at avoiding reproduction by pairs of thalassaemia carriers and the birth of homozygous children.During the four campaigns 138 501 students were examined, that is, 70 to 76% of those enrolled. Of these 3343 were found to be thalassaemic. Thus the overall prevalence of thalassaemia in Latium is 2.41 %, with minor fluctuations from one province to another and, above all, a slight, though definite, trend towards higher values in the southern part of Latium bordering on Campania.The screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…In a study from Italy it was stated that screening in schools did not create anxiety although no evidence for this comment was given (Silvestroni et al 1980). Follow-up will also be needed to find out what preventive action is taken following identification of the trait.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a study from Italy it was stated that screening in schools did not create anxiety although no evidence for this comment was given (Silvestroni et al 1980). Follow-up will also be needed to find out what preventive action is taken following identification of the trait.…”
Section: Discussionmentioning
confidence: 96%
“…Ante-natal screening for thalassaemia major has been undertaken in the U.K. (Ward et al 1983), and school screening for the beta thalassaemia trait has been carried out elsewhere (Silvestroni et al 1980). Ante-natal screening can only prevent thalassaemia major by termination of pregnancy whereas screening in schools could prevent thalassaemia major by altering the choice of the marriage partner.…”
Section: Introductionmentioning
confidence: 99%
“…All these possible misunderstandings are in contrast with data from this study and enquiries made among populations at risk showing that at least 80% of the well-informed multi-ethnic people in The Netherlands would choose for counseling and prevention in case of increased risk [18]. Additionally, many studies in other European, (North- and South) American and Islamic countries have shown a decrease in the number of affected children after proper information and counseling [19,20,21,22,23,24,25,26]. …”
Section: Discussionmentioning
confidence: 99%
“…The most common severe HBPs are: sickle cell disease (SCD) and thalassemia major (TM). Given their disease burden, the limited availability of therapy, and the effects on quality and duration of life, carrier testing programs have been implemented to facilitate primary prevention in many endemic countries (Silvestroni and Bianco, ; Silvestroni et al , ; Cao et al , ; Samavat and Modell, ; Leung et al , ; Bozkurt, ). Prevention is based on information, carrier screening, and counseling.…”
Section: Introductionmentioning
confidence: 99%